2000
DOI: 10.1046/j.1523-1755.2000.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial factor V expression colocalized with fibrin deposition in IgA nephropathy

Abstract: The present findings suggest that factor V is strongly expressed in mesangial cells in active IgAN accompanied with mesangial proliferation and may exert procoagulant activity, leading to intramesangial coagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…To discern the cellular expression of PMAT in the glomeruli, double immunofluorescence labeling was performed on human kidney cryosections using established cell type-specific markers for podocytes, mesangial cells, and glomerular endothelial cells-the three major cell types that make up the glomerulus. No overlap of specific PMAT staining was observed with ␣-smooth muscle actin (␣-SMA), a cell body marker for mesangial cells (13), or CD31, a cell surface marker for endothelial cells (24) (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…To discern the cellular expression of PMAT in the glomeruli, double immunofluorescence labeling was performed on human kidney cryosections using established cell type-specific markers for podocytes, mesangial cells, and glomerular endothelial cells-the three major cell types that make up the glomerulus. No overlap of specific PMAT staining was observed with ␣-smooth muscle actin (␣-SMA), a cell body marker for mesangial cells (13), or CD31, a cell surface marker for endothelial cells (24) (Fig. 3, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…3,25 In our previous study, factor V mRNA expression was observed in mesangial cells of IgA nephropathy with activity. 2 Taken together, the activation of local coagulation in the mesangial area may progress in MsPGN. Hung H-L and High KA reported that liver contained the highest amounts of factor X mRNA; however, factor X was also detected in various organs, including the kidney, at trace level.…”
Section: Roles Of Factor Xa In Rat Mspgnmentioning
confidence: 98%
“…These fixed sections were stained by an indirect method using a goat anti-mouse tissue factor antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA), a sheep anti-human factor V antibody (Cedarlane Laboratories), a goat anti-human factor X antibody (Santa Cruz Biotechnology), or a goat anti-mouse PAR2 antibody (Santa Cruz Biotechnology), as described previously. 2 Sections were then incubated with appropriate secondary antibodies, and color was developed as mentioned above. The specificity of the anti-PAR2 antibody was previously reported by blocking test, using specific immunizing blocking peptide.…”
Section: Histological Evaluation Of Renal Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…2,3) Also in human and experimental diabetic nephropathy, glomerular fibrin deposition and extracellular matrix (ECM) expansion have been noted. 4,5) In this context, transforming growth factor b (TGF-b) is upregulated in kidney diseases, and TGF-b promotes the production of various ECM proteins.…”
mentioning
confidence: 99%